PENGARUH PENGAWASAN DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN (BAGIAN PRODUKSI PT POLITAMA PAKINDO KABUPATEN SEMARANG) - Hendra Habiwibowo; Hari Susanta Nugraha (Universitas Diponegoro, 2018)
The purpose of this research is to find out the impact of supervision and physical work environment towards employees’ performance in the production division of PT Politama Pakindo. This research manages to be explanatory research. The population of this research involved 107 employees being in charge in production division. Sampling method used in this research is saturation sampling in which all 107 employees were examined. The data were analyzed quantitively. Analitical techniques used were validity test, realibility test, correlation coefficient, determination coefficient, univariate and multivariate regression test, T & J significance test. The result of this study shows that supervision causes some change in employees’ performance change as much as 40,8% simultaniously, physical work environment cause some change in employees’ performance change as much as 27,9% simultaniously, supervision along with physical work environment improve employee00s’ performance by 47.7%. The result of this study proves that supervision as well as physical work environment positively and significantly impact employees’ performance in both individual and team. It is recommended that PT Politama Pakindo needs to improve supervision, regular work result check to avoid possible mistake, provide safety, and also maintain regular equipment changing in accordance with the feasibility standard.